The Relationship between the World and Language in Bertrand Russell's Philosophy (Raparin Journal of Humanities (RJH), 2023)
In the contemporary philosophy and more specifically in philosophy of language, one of the essential issues of philosophical studies is the relationship between language, the World and knowledge about the world. Bertrand Russell as one of the leaders in logical analysis in contemporary philosophy considers logical foundation as significant pillar for language. He defines language, meaning knowledge in the context of logic and he forms the world in the logical facts. From here, a link between language and reality will be created, and thus there is an intention to break the other traditions.Bertrand Russell tried to write many books and essays and his literary heritage has become an important asset in philosophical discourses. This study aims under the Russell’s arguments to analyze the relationship between language and the world. It attempts from a different perspective to reach a different form of existence and world. This purpose helps in language activities in manifesting correct knowledge about the world that it has facts, events, state of affairs, reality and logic.Russell's attempts to connect between language and reality in the world produced many valuable arguments and thesis. This is on the foundation of logical analysis changes language to propositions and changes the world to facts instead of things. In addition, arranges all theories about meaning, descriptions, proper names and knowledge through the atomic propositions. Furthermore, he based his understanding to the external world, existing of things and the relations between them on logical language.